Surfactant TWEEN20 provides stabilisation effect on anthocyanins extracted from red grape pomace. (15th January 2019) - MohdMaidin, Nurmahani; Oruna-Concha, Maria Jose; Jauregi, Paula
Highlights: Surfactant has a protective effect on the anthocyanins. The stability of the anthocyanins increased with the concentration of TWEEN20. TWEEN20 and sorbic acid had comparable stabilisation effects. Malvidin was the most stable anthocyanin. CGA is a separation method that facilitates formulation of anthocyanins. Abstract: Red grape pomace, a wine-making by-product is rich in anthocyanins and has many applications in food and pharmaceutical industry. However, anthocyanins are unstable during processing and storage. This study aimed to investigate the stability of anthocyanins obtained by hydroalcoholic extraction (with and without sorbic acid) and colloidal gas aphrons (CGA) separation; a surfactant (TWEEN20) based separation. Anthocyanins in CGA samples showed higher stability (half-life = 55 d) than in the crude extract (half-life = 43 d) and their stability increased with the concentration of TWEEN20 in the CGA fraction (6.07–8.58 mM). The anthocyanins loss in the CGA sample (with the maximum content of surfactant, 8.58 mM) was 34.90%, comparable to that in the crude ethanolic extract with sorbic acid (EE-SA) (31.53%) and lower than in the crude extract (44%). Colour stabilisation was also observed which correlated well with the stability of individual anthocyanins in the EE and CGA samples. Malvidin-3-o-glucoside was the most stable anthocyanin over time.